KOMPOSISI DAN DOMINANSI GULMA KEBUN KELAPA SAWIT PADA TANAMAN BELUM MENGHASILKAN DAN TANAMAN MENGHASILKAN - Betty Yuniasih; A.T Soejono; Dzuk Ulinnuha (Program Studi Agroteknologi INSTIPER, 2017)
Weed is one of the problems in palm oil plantation. The research aims to determine the compositions and the dominance of the weeds in immature and mature stages then compare the weeds compositions between both. The research was conducted in Pelalawan Districk, Riau Province, from March to May 2017. The research was conducted by descriptive method. Sample was taken using a square plot measuring 1x1 meter with 10 replications. The plot sample was taken in a circle in immature plantings and in path mature plantings. The result shows that the diversity of the weeds was higher in immature plantings (18 species) than in mature stage (10 species). Weeds composition in palm oil plantation is much greater during the immature phase rather than mature phase because the high spaces and the high of sunlight in immature phase offer opportunity for the weeds to grow ubiquitously. None of the species in immature plantings are dominant species but in mature plantings there is one dominant species namely Nephrolepis bisserata. Perennial weeds species is a dominant weed type of both phase. The weeds compositions of immature and mature plantings shows the different compositions based on similarity index (IS Sorensen) that caused by the different environment condition. The weeds that found in mature plantings are a type of shade tolerant weeds. Nephrolepis bisserata, dominant species in mature plantings, is a shade tolerant species which can also increase air humidity and decrease the air temperature.